Weaning Away from Idolatry: Maimonides on the Purpose of Ritual Sacrifices - Klein, Reuven Chaim (Religions, 2021)
This essay explores Maimonides’ explanation of the Bible’s rationale behind the ritual sacrifices, namely to help wean the Jews away from idolatrous rites. After clearly elucidating Maimonides’ stance on the topic, this essay examines his view from different angles with various possible precedents in earlier rabbinic literature for such an understanding. The essay also shows why various other Jewish commentators objected to Maimonides’ understanding and how Maimonides might respond to those critiques. Additionally, this essay also situates Maimonides’ view on sacrifices within his broader worldview of the Bible’s commandments in general as serving as a counterweight to idolatrous rituals.